The quiet revolution in agrifood value chains in Asia: The case of increasing quality in rice markets in Bangladesh - Minten, Bart; Murshid, K. A. S.; Reardon, Thomas (International Food Policy Research Institute, 2011)
In Bangladesh—one of the poorest countries in Asia, where rice accounts for almost 70 percent of consumers' caloric intake—the share of the less expensive, low-quality coarse rice is shown to be rapidly decreasing in rice markets and the quality premium for the best-quality rice has been consistently on the rise in the last decades. It thus seems that the role of rice as only a cheap staple food is being redefined. The off-farm share in the final consumer price increases from 27 percent to 35 percent to 48 percent for low-, medium-, and high-quality rice, respectively, and the increasing demand for higher quality is thus seemingly associated with a more important off-farm food sector—in particular, milling, retailing, and branding—as well as a transformed milling industry. We further find that the labor rewards for and the technical efficiency of growing different rice qualities are not significantly different, and farmers do not benefit directly from consumers' increased willingness to pay for higher rice quality.